Geotechnical Properties of Fly Ash and its Application onSoft Soil Stabilization - Emiliani, Geliga; Dayangku Salma, Awang Ismail (Universiti Malaysia Sarawak (UNIMAS), 2010)
Soil stabilization has become the major issue in construction engineering and the researchers regarding the effectiveness of using industrial wastes as a stabilizer are rapidly increasing. This paper briefly describes the suitability of the local fly ash to be used in the local construction industry in a way to minimize the amount of waste to be disposed to the environment causing environmental pollution.